Mafia violence. Practices, meanings, consequences (Rivista di Studi e Ricerche sulla criminalità organizzata, 2019)
The article traces the scientific debate on mafia violence, starting from the study of Umberto Santino and Giorgio Chinnici (1989) who analyzed the murders and mafia warfares that took place in Palermo from the 1960s to the second half of the 1980s. Afterwards the article focuses primarily on the round table hosted by the Journal Meridiana in 2017, in which emeritus mafia scholars, belonging to different disciplines, have dealt with the issue; secondly on the book Mafia Violence, edited by Monica Massari and Vittorio Martone (Routledge, 2019), which  compares the characteristics and meanings of the violence in different Italian mafias and shows the results of a research project co-funded by the San Paolo Foundation and the Federico II University of Naples (carried out between 2015 and 2017), which have focused on the different forms of Camorra violence in Campania, especially in the Naples and Caserta areas.Keywords: Mafia, Violence, Italy, Camorra, trauma